1996
DOI: 10.1021/jm960324r
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomimetic Inhibitors of Herpes Simplex Virus Ribonucleotide Reductase with Improved in Vivo Antiviral Activity

Abstract: We have been investigating the potential of a new class of antiviral compounds. These peptidomimetic derivatives prevent association of the two subunits of herpes simplex virus (HSV) ribonucleotide reductase (RR), an enzyme necessary for efficient replication of viral DNA. The compounds disclosed in this paper build on our previously published work. Structure-activity studies reveal beneficial modifications that result in improved antiviral potency in cell culture in a murine ocular model of HSV-induced kerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…In vivo studies with some of the inhibitors developed by Moss et al [78] were even more enthusiastic since it was observed that the inhibitors were able to effectively reduce the severity of the virus in most of the cases, without interfering with the infected host. The latest developments of antisense technology allow to conclude that the inhibition of RNR can be performed in a pre-translation phase, which has several advantages over the other types of inhibition: i) they become very specific for the corresponding mRNA of that protein, and therefore of each organism and ii) taking this specificity in account it may decrease the toxicity or even the number of secondary effects that normally follows the other kind of inhibitors [65].…”
Section: Rnr Peptide Inhibition Began With the Discovery Bymentioning
confidence: 99%
“…In vivo studies with some of the inhibitors developed by Moss et al [78] were even more enthusiastic since it was observed that the inhibitors were able to effectively reduce the severity of the virus in most of the cases, without interfering with the infected host. The latest developments of antisense technology allow to conclude that the inhibition of RNR can be performed in a pre-translation phase, which has several advantages over the other types of inhibition: i) they become very specific for the corresponding mRNA of that protein, and therefore of each organism and ii) taking this specificity in account it may decrease the toxicity or even the number of secondary effects that normally follows the other kind of inhibitors [65].…”
Section: Rnr Peptide Inhibition Began With the Discovery Bymentioning
confidence: 99%
“…Hence, C-terminal Rnr2-based peptidomimetics (14-16) bind Rnr1, blocking RNR assembly and providing another mode of therapy for proliferative diseases such as cancer. Early reports on Rnr2 peptide-based inhibitors showed that they had in vivo efficacy against herpes simplex virus with nM dissociation constants (17)(18)(19), suggesting that similar potencies might be possible with anticancer peptidomimetics.…”
mentioning
confidence: 99%
“…20 In this latter work, reviewed in Ref. 21, assays of HSV-RR inhibition were performed under conditions that would be expected to favor R1 2 formation.…”
Section: Discussionmentioning
confidence: 99%